Factors determining necessity of application of combination actions in judo - Erastov, A. E.; Fomichev, A. A.; Igorevich, K.; Devyatyarova, E. A. (The Russian Journal of Physical Education and Sport, 2022)
As the main factors determining necessity of application of combination actions in judo, respondents noted predominance of combination actions in judo wrestling, as well as preferential application of attacking combination actions in judo. Respondents also drew attention to the need to differentiate combination actions based on the priorities of judokas, as well as to the use of counterattacking tactics of combination actions. High efficiency of combination actions of judoists, as well as necessity of application of preliminary combination actions for successful execution of footsteps and throws in judo are of great importance.